Strategic planning and its alignment with the budgeting process in selected national government departments - Matshidza, Namadzavho Violet (Vaal University of Technology, 2020)
South African government departments, through the relevant executing authority, are required to develop strategic plans in terms of the Public Service Amendment Act (Act No. 30 of 2007) and Public Finance Management Amendment Act (Act No. 29 of 1999). In terms of Treasury Regulation, 2005 section 6, the government departments are further required to comply with budgetary requirements. The key question in this research was to what extent is the strategic planning process aligned to the budgeting process. In light of the research question, the research objective was to investigate the alignment of the strategic planning and budgeting processes in the selected national government departments. In order to achieve the aforementioned research objective, structured questionnaires were distributed to 300 senior managers in the selected government departments of which 203 were completed and retrieved. The government departments that participated in the study were selected using the non-probability convenient sampling technique. A quantitative approach was followed, in which case a survey was used to garner data, which were analysed using statistical analytical methods, such as the means, standard deviations, exploratory factor analysis, correlation analysis and regression analysis. The five factors of strategic planning were extracted from the strategic planning questionnaire data and were coined strategic analysis and assessment (SAA), environmental impact assessment (EIA), goal setting (GS), responsibilities and resource allocation (RRA), and information system (IS). Correlation analysis indicated that there was a positive relationship between the five factors of the strategic planning process and the budgeting process. The regression analysis results confirmed the existence of a predictive relationship between the five factors of strategic planning and the budgeting process. The conclusion from this finding confirmed the alignment of strategic planning with the budgeting process in the selected national government departments. The internal consistency of the measuring instrument was tested by means of Cronbach’s alpha coefficient, while its validity was measured using face validity, content validity, construct validity, convergent validity and predictive validity. In spite of the positive correlation and regression analyses, recommendations were made to improve the strategic planning and budgeting processes.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Strategic planning; Budgeting; Budgeting process; Environmental impact assessment; Goal setting; Allocation of resources and information systems; Strategic analysis and assessment; Dissertations, Academic -- South Africa; Strategic planning; Finance, Public; Environmental impact analysis; Budget process -- Planning